Regional pest suppression associated with adoption of Cry1Ac soybean benefits pest management in tropical agriculture. Issue 10 (30th June 2022) - Horikoshi, Renato J; Dourado, Patrick M; Bernardi, Oderlei; Willse, Alan; Godoy, Wesley AC; Omoto, Celso; Bueno, Adeney de F; Martinelli, Samuel; Berger, Geraldo U; Head, Graham P; Corrêa, Alberto S
Abstract: BACKGROUND: Bacillus thuringiensis ( Bt ) crops have been adopted worldwide, providing high‐level protection from insect pests. Furthermore, Bt crops preserve natural enemies, promote higher yield, and economically benefit farmers. Although regional pest suppression by widespread Bt crop adoption has been observed in temperate regions, this possibility remains uncertain in tropical areas due to the high diversity of alternative hosts and mild winters. RESULTS: Evidence of regional reduction in insecticide use across areas was observed in Brazil where Cry1Ac soybean has been grown since 2013, with up to 50% reduction in the number of insecticide sprays for managing lepidopteran pests on non‐ Bt soybean observed at specific locations from 2012 to 2019. Pest monitoring data from four mesoregions across 5 years of commercial plantings of Cry1Ac soybean from December 2014 to July 2019 showed reduced numbers of Chrysodeixis includens moths captured in pheromone traps across years at all locations. The number of Helicoverpa spp. moths captured also was reduced at three locations. Conclusion: We provide evidence for regional suppression of lepidopteran pests and reduced insecticide use with the widespread adoption of Cry1Ac soybean in Brazil, bringing economic, social and environmental benefits. © 2022 Society of Chemical Industry. Abstract : Agriculture in Brazil is characterized by an intensive and large‐scale use of land, contributing to high pest pressure. This research data confirmed the regional pest suppression associated with the increasing adoption of Cry1Ac soybean by farmers in Brazil.